(untitled) (Academic Journal of International University of Erbil, 2026)
The observed rapid pace of climate change in Iraq, as well as worldwide, coupled with anthropogenic interventions such as agricultural and urban expansion, is threatening the integrity and sustainability of natural forests. In the Kurdistan Region of Iraq, oak forests constituting nearly 90% of the region’s forest cover are exhibiting alarming signs of decline, particularly in the Barzan area, where heartwood decay and hollowing of trunks have become prevalent across young and old trees. This study provides the first detailed multiparametric investigation into oak tree decline in Barzan forests, integrating field observations, SEM-EDX, XRD, and FTIR spectroscopy. FTIR-based indices revealed significant degradation of cellulose and hemicellulose, with lignin-to-cellulose ratios exceeding 1.0 in decayed samples. SEM-EDX analysis confirmed extensive fungal hyphal colonization and localized calcium oxalate biomineralization within heartwood tissues. XRD results showed a progressive decline in cellulose crystallinity index (from 51% in healthy to 35% in severely decayed wood). Tree ring width chronology (1928–2023) showed a declining growth trend, strongly correlating with rising temperatures and declining precipitation in the region. These findings suggest climate-driven fungal decay as the primary mechanism of oak forest deterioration in Kurdistan.